PROFILE OF PRIMARY HEADACHE PATIENTS IN NEUROLOGICAL POLYCLINIC - Yulia Damayanti; Eko Arisetijono Marhaendraputro; Widodo Mardi Santoso; Dessika Rahmawati (Journal of Pain, Headache and Vertigo, 2021)
Headache is the most common neurological disorder among all the symptoms of general health problems. Headaches are the most frequently complained of after back pain, which brings someone to the doctor and harms personal, family, social, quality of life, work, and finances. This study aims to find out the characteristics of primary headache patients in the neurological polyclinic, RSUD dr. Saiful Anwar Malang. The design of this research was an observational descriptive study of the filled headache questionnaire was to determine the characteristics of headache patients who visited the neurological polyclinic at dr. Saiful Anwar Malang with complaints of primary headache. The procedure of this research is to provide a questionnaire. The data analysis technique used is that the research variables will be presented in the frequency distribution table. The results of this research show that primary headache was more common in women as many as 19 people (61%) compared to male 12 people (39%). Most of the primary headache patients who came to the neurological clinic of Saiful Anwar Hospital were 30-60 years old. Tension-Type Headache (TTH) in this study had the highest percentage of 58%. In this study, cluster headache two patients all attacked women.